Bilateral Isolated Spherophakia in Two Young East European Siblings: A Case Report - Silvia Babighian (Karger Publishers, 2021)
A 19-year-old Caucasian woman was referred to the emergency room and thereafter to the department of ophthalmology complaining for bilateral decrease of visual acuity and severe pain. A complete ophthalmological evaluation was performed. Best-corrected visual acuity (BCVA) was LogMAR 0.3 in the right eye (RE) and LogMAR 0.5 in the left eye (LE). Intraocular pressure (IOP) was 28 and 38 mm Hg in the RE and LE, respectively. The patient showed a shallow anterior chamber and spherical equivalent refractive error −29.0 diopters (D) in the RE and −30.0 D in the LE. The diagnosis of bilateral angle closure glaucoma, secondary to highly myopic, forward dislocated lens was made, in the setting of spherophakia. The ultra-sound biomicroscopy images confirmed the diagnosis. Clear lens extraction was promptly performed with resolution of ocular hypertension and restoration of BCVA. In view of the frequent systemic association, family members also underwent ophthalmological evaluation. The 13-year-old sibling showed mild myopia and borderline IOP. He was administered topical β-blockers and observation. Genetic counseling did not reveal mutations usually associated with spherophakia or systemic conditions. This case report highlights the variable spectrum of clinical expression in spherophakia; therefore, ophthalmological treatment should be tailored according to clinical presentation. Systemic evaluation and genetic counseling are also recommended in the suspicion of spherophakia.